Correlation Beetwen Body Weight with Scrotal Circumference, Testis Weight and Sperm Production of Boer Buck Intensively Rearing - I Wayan Lanus Sumadiasa Wayan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Body weight of one of the regulators that determine the scrotum circumference and weight (large) testicles. Next, the weight of the testes has a very close relationship with sperm production that will determine the reproductive ability of a male. The purpose of this study was to determine the relationship between body weight and scrotum circumference, testicular weight and boer goat sperm production that was maintained intensively. The study was conducted with a descriptive method with the material of 15 male goats owned by PT. Sadhana Arif Nusa. Data is processed by regression and correlation analysis using the SPSS program. The results showed that the body weight average was 52.58 ± 14.96 kg, correlated very significantly (p <0.01) with scrotum circumference (25.68 ± 1.96 cm) and testicular weight (0.46 ± 0, 10 kg) with a correlation coefficient of 0.67 and 0.91. Body weight not correlated (p> 0.05) with good sperm production volume (0.50 ± 0.19 ml), pH (6.43 ± 0.19), sperm consistency, progressive motility (73.33 ± 7, 24 %) and Spermatozoa concentration (2.18 ± 0.54 x 109/ml). The scrotum circumference is very significantly correlated (p <0.01) with a testicular weight and a real correlation (p <0.05) with sperm volume, motility and concentration of spermatozoa with a coefficient of 0.91 each; 0.58; 0.56 and 0.54. The testes weight is real correlating (p <0.05) with sperm volume, progressive motility and spermatozoa concentration with a coefficient of 0.53 each; 0.56 and 0.54. CONCLUSION, body weight correlates piosif with scrotum circumference, the weight of the quality of the testes and sperm production in boer goats.